IMPLEMENTASI GERAKAN LITERASI SEKOLAH DALAM MENUMBUHKAN BUDAYA LITERASI DI SMP NEGERI 2 PONTIANAK - Normala, Normala; Hanum, Atiqa Nur Latifa; Amir, Amriani (Universitas Tanjungpura, 2024)
Gerakan Literasi Sekolah (GLS) is one of the government's initiatives to address the issue of students' poor interest in reading in Indonesia. This research was carried out with the purpose of determining how the implementation of GLS at SMP Negeri 2 Pontianak. This study employs research methodologies based on a case study methodology. In order to collect data, in-depth observations and interviews with eight informants were conducted. Data reduction, data presentation, and conclusion drafting are data analysis techniques employed in this study, while the triangulation approach is used to measure validity. The findings revealed that the School Literacy Movement at SMP Negeri 2 Pontianak was implemented in stages of habituation, development, and learning. The habituation step involves students reading non-lesson books for 15 minutes, followed by the development stage, in which they are requested to reply to the book in the form of a summary. Students are expected to convey the outcomes of literacy exercises in various types of work during the learning stage. Faces challenges such as a shortage of library resources, a lack of enthusiasm, and parental support. To address this issue, attempts are being made to urge students to produce reading materials individually and then trade reading materials with classmates, to socialize pupils about the value of literacy, and to develop literacy drive. The ultimate result is that the implementation of Gerakan Literasi Sekolah in developing a literacy culture at SMP Negeri 2 Pontianak went well, but not optimally since there are still hurdles in its implementation.